SUGGESTIVE SPEECH ACTS USED FOR HYPNOTHERAPY OF ANXIETY DISORDER CASES - Oktavianus, Oktavianus; Santi, Sisca Oktri; Usman, Fajri (LINGUA LITERA : journal of english linguistics and literature, 2025)
This study examines speech acts of suggestive language in individuals experiencing anxiety disorders within hypnotherapy practice. The research investigates the types of speech acts used during hypnosis sessions with a client experiencing anxiety. This study employs a qualitative descriptive approach, grounded in speech act theory by Austin (1962), Searle (1969), and Wijana (1996). Data were collected using the observation method. We presented he findings informally, explaining the results in the author's own words.We obtained from a single hypnotherapy session involving a client with anxiety. The results indicate six types of suggestive language used in hypnosis: suggestions, commands, prohibitions, statements, expressions of praise, and questions. Suggestive language, in the form of questions, encourages reflection and internal decision-making in the Client, without issuing direct commands, in accordance with direct and indirect non-literal speech acts. Suggestive language in the form of questions highlights a linguistic gap between conventional theory and hypnotherapy practice, opening new avenues for development in pragmatics and applied linguistics, particularly in therapeutic communication.